Az életminőség területi differenciái Magyarországon: A kistérségi szintű HDI becslési lehetőségei - András Csite; Nándor Németh (Hungarian Academy of Sciences, Institute of Economics, 2007)
– The study focuses on the quality of live disparities among Hungarian micro-regions as well as among counties. For measuring quality of life HDI was chosen as the index to work with. The analysis focused on three years (1994, 2001 and 2005), which makes it possible to examine the temporal change in regional disparities over a ten-year period. This choice was supported by the fact that this way it became possible to make international comparisons on the subnational levels and the outcomes could be compared with the HDI calculations of the previous years. While we acknowledge the limits of the applicability of HDI for studying regional differences in the quality of life, we also see a number of advantages in using it. Our analysis proved that Hungarian micro-regions are in distinct relative position regarding the various dimensions of development. From among the components of HDI level of education shows the lowest while economic production the highest degree of regional disparities. Between the early 1990s and 2005 the value of HDI increased in all the microregions. In the same period, on the national level disparities in quality of life among the microregions decreased, while among counties and regions they did grow. Consequently, the choice of territorial level substantially influences research outcomes we get regarding the problematic of convergence-divergence. Between 1994-2001 and 2001-2005 the positive regional auto-correlation increased, thus it seems that the location of the micro-regions plays an increasingly important role in the explanation of the disparities in their level of development. According to the accessible HDI research results a further assumption can be made: East-Central European countries can be characterised with similar transformation patterns in the past 15 years concerning changes in the regional development patterns. Two of the most significant achievements of our study are taking into account the possibilities of micro-regional HDI estimations and elaborating a possible methodology.
Keywords: O15; O18; R11; 330; Human Development index; quality of life; micro-regions; regional inequalities; spatial autocorrelation; Lebensqualität; Räumliche Verteilung; Entwicklungsindikator; Ungarn